Rights and duties in predictive medicine. Synthesis and considerations about a recent meeting - Mele, Vincenza (Medicina e Morale, 1991)
The author analyses the positions of "laical" bioethics (subjectivistic bioethics) about predictive medicine comparing with the "catholic'" ones (personalistic bioethics), taking a recent meeting about this argument as a starting point. Bioethics and predictlve medicine is dealt in prenatal and in postnatal diagnosis. Thc author refers to two different principles which constitute the basis of physical life's defence (for personalistic bioethics) and the principle of autonomy (for subjectivistic bioethics).